ANALISIS KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA GURU HONORER SMKS PANCA BHAKTI SUNGAI RAYA - Peri, Peri; Achmadi, Achmadi; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This study aims to determine the causes of decreasing/increasing performance of honorary teachers in Panca Bhakti Sungai Raya vocational high school. The method used in this study is to use a qualitative research approach. The source of the data in this study is the economic subject teacher of Panca Bhakti vocational high school, amounting to 6 teachers. The techniques used in data collection are direct observation techniques, direct communication and documentary study techniques. While the data collection tools are interview guidelines, observation and triangulation sheets. The data processing technique uses qualitative analysis techniques. The results of the study are based on the results of interviews and observations, and then analyzed. So, it can be concluded that the cause of the increase or decrease in the performance of honorary teachers in Panca Bhakti Sungai Raya vocational high schools is seen from the compensation factor with the following aspects: Salary, Incentives, Allowance, and Facilities. Furthermore, the work motivation factors with the following aspects: Internal motivation and external motivation From the results of interviews with teachers and curriculum officers from the results of observations it can be concluded that compensation and work motivation can increase and decrease the performance of the honorary teachers.Â Keywords : Performance of Honorary Teachers in Economic Subjects